2005
DOI: 10.1016/j.limno.2005.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nutrients and zooplankton community structure on phytoplankton growth in a subtropical Australian reservoir: An enclosure study

Abstract: Patterns of zooplankton-phytoplankton interactions in subtropical lakes of the Southern Hemisphere may deviate from those established for north-temperate lakes. We tested the responses of phytoplankton growth to different community structures of zooplankton and nutrient enrichment in a subtropical Australian reservoir for the prediction of potential outcomes of lake biomanipulation. Two zooplankton communities were created in lake enclosures over 4 weeks: a rotifer-dominated community developed in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 33 publications
3
31
1
Order By: Relevance
“…This result corroborates whith argued that juvenile fish affect plankton, reducing the densities of some organisms and consequently, enabling the population growth of other species, altering the zooplankton structure (Gerking, 1994, Qin et al, 1995Keefe et al, 1998;Böing et al, 1998;SASS et al, 2014). An association between consumption of larger sized zooplankton organisms with reduced grazing on phytoplankton and consequent increase in biovolume of this community has been described by several authors (Matheus & Barbiere, 1999;Pegano et al, 1999;Hunt & Matveevb, 2005 The effect of the larvae of different fish species on the assemblage of copepods was not observed by Guest et al (1990), which differs from the results obtained here in, which may be related to larval diet in both studies. On the other hand, these authors observed effects of larvae of different fish species on cladocerans, different from that found in the present study, in which the density and biovolume of cladocerans was not different between tanks with different species and even the control tank.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This result corroborates whith argued that juvenile fish affect plankton, reducing the densities of some organisms and consequently, enabling the population growth of other species, altering the zooplankton structure (Gerking, 1994, Qin et al, 1995Keefe et al, 1998;Böing et al, 1998;SASS et al, 2014). An association between consumption of larger sized zooplankton organisms with reduced grazing on phytoplankton and consequent increase in biovolume of this community has been described by several authors (Matheus & Barbiere, 1999;Pegano et al, 1999;Hunt & Matveevb, 2005 The effect of the larvae of different fish species on the assemblage of copepods was not observed by Guest et al (1990), which differs from the results obtained here in, which may be related to larval diet in both studies. On the other hand, these authors observed effects of larvae of different fish species on cladocerans, different from that found in the present study, in which the density and biovolume of cladocerans was not different between tanks with different species and even the control tank.…”
Section: Discussioncontrasting
confidence: 54%
“…Shifts in the dominant zooplankton species lead to changes in the phytoplankton (Watson, Bayne, Devries, & Williams, 2003;Hunt & Matveevb, 2005;Soares & Hayashi, 2005). Lower biomass of phytoplankton in environments with high biomass of Daphnia galeata were observed by Urabe (1990), and Böing et al (1998) reported lower biovolume of phytoplankton with increasing clearance rate by D. galeata.…”
Section: Introductionmentioning
confidence: 99%
“…Iriarte and Purdie, 2004;Jasprica and Hafner, 2005;Henson et al, 2006;Miller and Harding, 2007;Peeters et al, 2007a) or on the effect of nutrient on phytoplankton biomass (e.g. Hunt and Matveev, 2005;Beamud et al, 2007;Ç elik and Ongun, 2008;Kasprzak et al, 2008;Katano et al, 2008 Tirok and Gaedke (2007) investigated the individual and combined effects of three physical variables (irradiance, temperature and water stability) on algal dynamics using descriptive statistics, multiple regression models and a process-oriented dynamic simulation model, few studies has tried to reveal the relative importance of local (e.g. spatial heterogeneity) and regional (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the different usages, the reservoirs showed different nitrogen sources (Boyer et al 2002), resulting in probable distinct responses in the composition of the main food (phytoplankton) and, consequently, zooplankton (Burford and Pearson 1998, Hunt and Matveev 2005, Bozelli et al 2009). Ammonia, for example, which is predominant in the highly altered reservoirs (Borborema and Saco I), is easily assimilated by phytoplankton.…”
Section: Discussionmentioning
confidence: 99%
“…However, the different sources of pollution and the deterioration of water quality can lead to a differentiated composition of the community (Burford and Pearson 1998, Hunt and Matveev 2005, Bozelli et al 2009), even in systems located close to each other. And, this can be used as a tool to indicate the environment condition and help in management.…”
Section: Introductionmentioning
confidence: 99%